DYNAMICS OF CALCIUM AND PHOSPHORUS IN THE ORAL FLUID IN PRESCHOOL CHILDREN WITH ADENOID HYPERTROPHY IN VIEW OF PREVENTIVE MEASURES AGAINST CARIES - L.F. Kaskova; L.P. Ulasevych (Український стоматологічний альманах)
The main factor of dental hard tissues caries increasing is the indicator of supersaturation of calcium and phosphorus in oral liquid, which is the key to the equilibrium of enamel re- and demineralization.